Health education on diabetes at a South African national science festival - M Mhlongo; P Marara; K Bradshaw; S Srinivas (South African Medical Association, 2018)
Background. Diabetes is one of the non-communicable diseases with a major negative impact on the health and development of South Africans. Empowering the population’s understanding of the condition, with health-literacy appropriate approaches, is one of the interventions that allows discussions around the prevention of diabetes.Objective. To determine the effects of a health education programme on increasing knowledge about diabetes and encouraging preventive measures.Method. A public health education exhibition was held by a pharmacy student at a national science festival. It incorporated presentations, posters, health models, word-search games, information leaflets and a computer-based quiz consisting of pre- and post-intervention questions.Results. Junior and senior school learners participated in the computer-based quiz. Results from the junior school pre-intervention phase showed that learners had a fair prior knowledge of diabetes, with an overall score of 52.8%. Improvement in their overall mean score at the 5% significance level was noted (p=0.020). There was a significant difference in the mean score after the intervention at the 1% level (government schools: 65.5 (standard error (SE) 3.1)%, independent schools: 45.9 (6.2)%; p=0.006). Of the senior learners 53.7% (n=137) indicated that they use computers at school, while 118 (46.3%) did not have access to computers. The improvement in overall knowledge of the senior participants after the intervention was significant at the 0.1% level (p<0.001).Conclusion. The health education offered by the pharmacy student's project was interactive and used an interdisciplinary approach to improve health literacy and raise awareness of diabetes. This is a tested intervention that may be adopted for improving health literacy among schoolchildren.